Synthesis, Structure and DFT Calculation of Chlorimuron-ethyl - Chen, Pei-Quan; Tan, Cheng-Xia; Weng, Jian-Quan; Liu, Xing-Hai (Asian Journal of Chemistry, 2012)
The commercial herbicide chlorimuron-ethyl (C15H15ClN4O6S, Mr = 414.82) was synthesized and its structure was studied by X-ray diffraction. The crystals are triclinic, space group P-1 with a = 7.831(3), b = 12.324(5), c = 20.242(8) Å, a = 94.941(7), b = 97.426(7), g = 93.658(7)º. Theoretical calculation of chlorimuron-ethyl was carried out with B3LYP/6-31G (d,p). The full geometry optimization was carried out using 6-31G(d,p) basis set and the frontier orbital energy. This result is in accord with the result analyzed by the Frontier molecular orbital theory.